ALTERNATIVE SOLUTION FOR DIRECT TRANSFORMATION OF GEOGRAPHIC INFORMATION: THE CASE OF COSTA RICA CHANGING THE OFFICIAL SYSTEM OF COORDINATES (LAMBERT TO CRTM05) - Ramírez-Núñez, Manuel (2015)
For many years, Costa Rica officially used cartography based on the Lambert projection system, datum Ocotepeque. In 2007 the official reference system was changed to CR05, forcing public institutions to transform all their cartography to this new system. This change affects the way new spatial information is generated and also involves the transformation of all the previous cartography to the country’s new official system. Therefore, it’s necessary for these institutions to establish an appropriate methodology for the conversion, considering the scale and accuracy of their cartographic products. This paper proposes a methodology that allows for direct transformation of the spatial data contained in the former system to the official reference system CR05. The results of this research provide public and private institutions alike in Costa Rica a simple and efficient method to transform their digital maps by setting up Geographic Information System platforms, thus reducing the costs and time in converting their data.